FERMENTED AND NON-FERMENTED WHOLE RICE BRAN IN THE PRODUCTION OF THE ROTIFER Brachionus plicatilis - Lídia Sousa MONTEIRO; José María MONSERRAT; Anelise CHRIST-RIBEIRO; Eliana Badiale FURLONG; Marcelo Borges TESSER (Boletim do Instituto de Pesca)
The objective of the present study was to evaluate the use of fermented and non-fermented whole rice bran for rotifer feeding, based on the effects on growth parameters, antioxidant and oxidative damage responses, and water quality. The study was based on three experiments, which compared the effect of different concentrations of non-fermented whole rice bran, the effect of different concentrations of fermented whole rice bran and the effect of the best concentrations of fermented and non-fermented whole rice bran, as well as the replacement of part of the baking yeast by rice bran. The results showed the best growth performances in treatments with 0.7 g yeast with 1.5 g fermented rice bran, 0.35 g yeast with 0.75 g whole rice bran, and 0.35 g yeast with 0.75 g fermented rice bran. Fermentation of rice bran for 6 hours did not induce oxidative stress in rotifers. This work revealed that the use of 1.5 g of fermented bran and replacement of 50% of yeast with fermented or non-fermented rice bran may be used for rotifer feeding, with the additional benefit of improving the environmental quality due to the lower amount of ammonia released in the water.